Second Five Year Plan (1956-61) Bombay State, Statement A, Plan Expenditure - Planning Commission (Planning Commission, 1955)
An abstract showing the important targets proposed under the Second Five Year Plan of Bombay State is appended. The salient features are brought out below - Agriculture Improved Seeds During the First Five Year Plan the area covered by improved varieties increased from acres to,64 lakhs of acres. It is now proposed to organise Seed Multiplication Farms in each taluka or Development Block and the total area to be brought under improved seed including National Extension Service and community Development Project Blocks will be 177 lakhs of acres.
Bombay State